2011
DOI: 10.1038/jhh.2011.95
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 4 weeks of aerobic exercise on vascular and baroreflex function of young men with a family history of hypertension

Abstract: The effect of short-term aerobic exercise on vascular function of young individuals with a family history of hypertension was investigated. Thirty young men with a family history of hypertension were randomly assigned to either an exercise (n ¼ 15) or control (n ¼ 15) group. Exercise subjects performed 30 min of supervised cycle training at 65% of their maximal oxygen uptake ( . VO 2max ), three times per week for 4 weeks. Control subjects were asked to maintain their normal levels of physical activity. Peak l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 37 publications
1
21
0
5
Order By: Relevance
“…These reductions in MAP and AIx suggest an improvement in the functionality of the resistance arteries and therefore a reduction in CV risk. The results were novel (in the context specifically of green-exercise) but expected, as aerobic exercise programmes have previously been associated with improvements in CV risk and vascular haemodynamics, including MAP and AIx [53][54][55]. However, to the best of our knowledge, while Pretty et al [21] have demonstrated the beneficial impact of acute bouts of aerobic exercise whilst viewing scenes of nature on MAP, the effect of an 8-week green-exercise programme on MAP and AIx had not before been investigated.…”
Section: Discussionmentioning
confidence: 85%
“…These reductions in MAP and AIx suggest an improvement in the functionality of the resistance arteries and therefore a reduction in CV risk. The results were novel (in the context specifically of green-exercise) but expected, as aerobic exercise programmes have previously been associated with improvements in CV risk and vascular haemodynamics, including MAP and AIx [53][54][55]. However, to the best of our knowledge, while Pretty et al [21] have demonstrated the beneficial impact of acute bouts of aerobic exercise whilst viewing scenes of nature on MAP, the effect of an 8-week green-exercise programme on MAP and AIx had not before been investigated.…”
Section: Discussionmentioning
confidence: 85%
“…Realmente, já é bem estabelecido na literatura que o treinamento físico aeróbio e/ou resistido é capaz de promover melhora estrutural e/ou funcional nos vasos arteriais de indivíduos saudáveis 12,16 e com doenças cardiovasculares 13,15,19,20 . Nesse contexto, estudos que aplicaram treinamento físico em população saudável, porém filhos de um ou ambos os pais hipertensos, observaram melhoras em alguns mecanismos de controle da função vascular que podem justificar nossos resultados 21,22 . Estudo conduzido por Ciolac et al 21 observou o efeito do treinamento físico aeróbio realizado em esteira ergométrica sobre os níveis de óxido nítrico, endotelina-1, noradrenalina e velocidade de onda de pulso em mulheres jovens, filhas de hipertensos.…”
Section: Discussionunclassified
“…Similarmente, Goldberg et al 22 observaram em homens jovens filhos de hipertensos o efeito do treinamento físico aeróbio realizado em cicloergômetro de membros inferiores e prescrito a 65% da frequência cardíaca máxima, com sessões de 30 minutos, três vezes por semana, durante quatro semanas. Os resultados encontrados corroboram mais uma vez os nossos achados.…”
Section: Discussionunclassified
See 2 more Smart Citations